The measurement of drug-induced interferon γ-releasing cells and lymphocyte proliferation in severe cutaneous adverse reactions - N. Suthumchai (2018)
© 2018 European Academy of Dermatology and Venereology Background: The lymphocyte transformation test (LTT) is a standard laboratory method to identify culprit drugs in patients with a history of drug-induced non-immediate hypersensitivity and is mainly performed during the recovery phase. The measurement of drug-specific interferon γ (IFN-γ)-releasing cells has been introduced to confirm culprit drugs, even during the acute phase of drug allergy. Objectives: This study aimed to evaluate the capability of the enzyme-linked immunospot assay (ELISpot) to detect drug-specific IFN-γ-releasing cells during the acute phase and the capability of LTT to identify culprit drugs during the recovery phase in patients presenting with severe cutaneous adverse reactions (SCARs). Methods: Peripheral blood mononuclear cells (PBMCs) from 23 SCAR patients were collected during the acute and recovery phases and assayed for drug-specific IFN-γ-releasing cells and lymphocyte proliferation, respectively. Results: Drug-specific IFN-γ-releasing cells were detectable in 73.9% of SCAR subjects (55.6% and 85.7% in patients who were and were not taking systemic steroids, respectively), whereas LTT results were positive in 52.2% of SCAR subjects. The frequencies of drug-specific IFN-γ-releasing cells were significantly higher in patients with positive LTT than in those with negative LTT (260.1 ± 110.0 and 46.6 ± 20.7 cells/106PBMCs, P = 0.01). A significant correlation between the results of the IFN-γ ELISpot assay and LTT was demonstrated (r = 0.65, P value <0.01). Conclusion: The IFN-γ ELISpot assay could be a useful tool to identify culprit drugs in SCAR patients when culprit drug identification is urgently needed during the acute phase of drug allergy.